Filipino Communication Style as Reflected in Politeness Strategies in Administrative Memoranda in the Philippine Workplace - Agnir-Paraan, Lucris Carina N. (Journal of English Studies and Comparative Literature; Vol 18 No 2 (2019), 2019)
This study explores the interplay of language and culture in the crosscultural interaction of the western-oriented memorandum and its writers’Filipino culture. It uses focused ethnography and content analysis to examine politeness strategies (PS) in 100 memoranda to see how culture is reflectedin the choice of PS. In place of Brown & Levinson’s (B&L) ‘face’ is offered aFilipino construct of tao (person) with a strong sense of kapwa (shared inneridentity). An alternative taxonomy of PS is also offered to show how a Filipino perspective addresses positive and negative ‘faces’ but not necessarily inmutually exclusive categories. The dominant choice of PS suggests that writers of memoranda consider the threat of readers feeling imposed upon more than that of not being admired, and desire to preserve relationships and protect others’ self-worth, while also addressing dislike for directness and in-group orientation. Non-prescribed linguistic features are also consistent with Filipino communication styles.